If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 10 = 5 + -1a Reorder the terms: 10 + 5a = 5 + -1a Solving 10 + 5a = 5 + -1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. 10 + 5a + a = 5 + -1a + a Combine like terms: 5a + a = 6a 10 + 6a = 5 + -1a + a Combine like terms: -1a + a = 0 10 + 6a = 5 + 0 10 + 6a = 5 Add '-10' to each side of the equation. 10 + -10 + 6a = 5 + -10 Combine like terms: 10 + -10 = 0 0 + 6a = 5 + -10 6a = 5 + -10 Combine like terms: 5 + -10 = -5 6a = -5 Divide each side by '6'. a = -0.8333333333 Simplifying a = -0.8333333333
| 3-3x=-18 | | x+256=-412 | | (3y-4)=(3y-5-4y)-(2-5y+10) | | 7x+9+16x=-21 | | x^2-10x-5=x^2-11x+10 | | 8/9(z-1)=-84 | | 2.86w-8.1258=-3.75 | | 2x^2=x+9 | | 2.43+f=7.6 | | (3x+12)-7=(x+5)+2x | | 5l=25s | | m+12n+18-11n+17-4m= | | Y-38=19 | | 2/x-5/6/x-3 | | 28=0.10-12 | | 90=2+(3m) | | 8n-4n*2+8n= | | 2cos+sec=3 | | 6(x+10)-2(3x+30)=0 | | 9(0.1111111111+-0.5555555556y)+5y=1 | | 6(x+10)-2(2x+30)=40 | | (2x-5)=(2x+6) | | 17s=221 | | 3/4÷9 | | 3-1(2y+-5)=7-2(y+1) | | 52v=156 | | 6÷1/2 | | 6(x+10)-2(3x+30)=40 | | 6(x+10)-2(3x+30)=4x-10 | | 26+10p=36+8p | | 5x+4=289 | | 6(k+8)+7k=-8 |